Perioperative baseline β-blockers: An independent protective factor for post-carotid endarterectomy hypertension. (April 2021) - Teng, Lequn; Fang, Jie; Zhang, Yongbao; Liu, Xinnong; Qu, Chengjia; Shen, Chenyang
Objective: Post-carotid endarterectomy hypertension is a well-recognized phenomenon closely related to surgical complications. This study aimed to determine whether different kinds of perioperative antihypertensive drugs had a protective effect on post-carotid endarterectomy hypertension and influence on intraoperative hemodynamics. Method: We retrospectively investigated 102 carotid stenosis patients who underwent conventional endarterectomy with a perioperative baseline antihypertensive regimen. Post-carotid endarterectomy hypertension was defined as a postoperative peak systolic blood pressure ≥160 mmHg and/or a requirement for any additional antihypertensive therapies. We compared the clinical characteristics and types of baseline perioperative antihypertensive drugs between patients with and without post-carotid endarterectomy hypertension and then determined the significant independent effect of antihypertensive drugs on post-carotid endarterectomy hypertension through multivariate regression and detected their influence on intraoperative hypertension (induction-related systolic blood pressure and vasodilators consumption) and hemodynamic depression (intra-arterial systolic blood pressure ≤100 mmHg and/or heart rate ≤50 beats/min). We also investigated adverse events such as stroke, death, myocardial infarction, and cerebral hyperperfusion syndrome during the postoperative hospitalization. Results: A total of 52/102 (51.0%) patients were defined as having post-carotid endarterectomy hypertension during the first three days postoperative, including eight patients with a postoperative systolic blood pressure that exceeded 160 mmHg at least once, 31 patients requiring postoperative antihypertensive treatment in addition to their baseline regimen, and 13 patients with both. The incidence of stroke/death/myocardial infarction and cerebral hyperperfusion syndrome after conventional endarterectomy during hospitalization were both 1.9%. A significantly increased risk of composite postoperative complications (including cerebral hyperperfusion syndrome, hyperperfusion-related symptoms, transient ischemic attacks, stroke, death, and cardiac complications) was observed in patients with post-carotid endarterectomy hypertension than without (15.4% versus 2.0%, p  = 0.032). Patients free of post-carotid endarterectomy hypertension had a higher incidence of perioperative baseline β-blocker use than patients who suffered from post-carotid endarterectomy hypertension (46.0% versus 21%, p  = 0.008). In multivariate analysis, β-blocker use was a significant independent protective factor for post-carotid endarterectomy hypertension (OR = 0.356, 95% CI: 0.146–0.886, p  = 0.028). Patients taking β-blockers had a lower postoperative peak systolic blood pressure than the β-blocker-naïve population (137.1 ± 12.1 mmHg versus 145.0 ± 11.2 mmHg, p  = 0.008), but the postoperative mean systolic blood pressure showed no intergroup difference. However, the incidence of hemodynamic depression during conventional endarterectomy was higher in patients with perioperative β-blocker use than in those without (44.1% versus 25.0%, p  = 0.050). The difference in intraoperative hemodynamic depression became more prominent between the β-blocker and non-β-blocker groups (81.8% versus 33.3%, p  = 0.014) for whose preoperative baseline heart rate was equal to or lower than 70 beats/min. Conclusion: The perioperative use of β-blockers is a protective factor for post-carotid endarterectomy hypertension and contributes to stabilizing the postoperative peak systolic blood pressure three days after conventional endarterectomy. However, β-blockers might also lead to intraoperative hemodynamic depression, especially for patients with a low baseline heart rate.